Effects of Long-Term Type I Interferon on the Arterial Wall and Smooth Muscle Progenitor Cells Differentiation. Issue 2 (February 2016) - Diao, Yanpeng; Mohandas, Rajesh; Lee, Pui; Liu, Zhiyu; Sautina, Larysa; Mu, Wei; Li, Shiyu; Wen, Xuerong; Croker, Byron; Segal, Mark S.
Abstract : Objective—: Patients with systemic lupus erythematosis are at risk for premature atherosclerosis and half of the patients with systemic lupus erythematosis have elevated type I interferon (IFN-I) levels. We hypothesized that IFN-I would induce premature atherosclerosis by increasing the number of smooth muscle progenitor cells (SMPC) in the bloodstream and promoting atherosclerotic lesions within the vasculature. Approach and Results—: SMPC isolated from wild-type and IFN receptor knockout animals were cultured in medium±IFN-I. In vivo, we used electroporation to generate stable IFN-I expression for as long as 4 months. The number of SMPC was determined in mice that expressed IFN-I and in control mice and sections from the bifurcation of the abdominal aorta were analyzed 3 months after electroporation of an IFN-I expression plasmid or a control plasmid. Adding IFN-I to the media increased the number of cultured wild-type SMPC and increased mRNA for SM22, but had no effect on SMPC isolated from IFN receptor knockout mice. Our in vivo results demonstrated a positive relationship between the preatherosclerotic-like lesions and endothelial damage. Although, there were no significant differences in smooth muscle cell density or thickness of the medial layer between groups, the IFN-I–expressing mice had a significant increase in preatherosclerotic-like lesions and immature smooth muscle cells, cells that expressed CD34 and smooth muscle α-actin; but lacked smooth muscle myosin heavy chain. Conclusions—: IFN-I seems to enhance SMPC number in vitro. In vivo IFN-I expression may maintain SMPC in an immature state. These immature smooth muscle cells could give rise to macrophages and eventually foam cells. Abstract : Supplemental Digital Content is available in the text.